If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -1(x + -1) = -1(x + -1) + 3x Reorder the terms: 4x + -1(-1 + x) = -1(x + -1) + 3x 4x + (-1 * -1 + x * -1) = -1(x + -1) + 3x 4x + (1 + -1x) = -1(x + -1) + 3x Reorder the terms: 1 + 4x + -1x = -1(x + -1) + 3x Combine like terms: 4x + -1x = 3x 1 + 3x = -1(x + -1) + 3x Reorder the terms: 1 + 3x = -1(-1 + x) + 3x 1 + 3x = (-1 * -1 + x * -1) + 3x 1 + 3x = (1 + -1x) + 3x Combine like terms: -1x + 3x = 2x 1 + 3x = 1 + 2x Add '-1' to each side of the equation. 1 + -1 + 3x = 1 + -1 + 2x Combine like terms: 1 + -1 = 0 0 + 3x = 1 + -1 + 2x 3x = 1 + -1 + 2x Combine like terms: 1 + -1 = 0 3x = 0 + 2x 3x = 2x Solving 3x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3x + -2x = 2x + -2x Combine like terms: 3x + -2x = 1x 1x = 2x + -2x Combine like terms: 2x + -2x = 0 1x = 0 Divide each side by '1'. x = 0 Simplifying x = 0
| 2(3x-5)+x=12x-41solve | | a/2+a/3+a/4 | | 1/2*1/3 | | 3(6-x)=12 | | 1+z=2 | | 5w+10=5+8w | | -5(4x-8)=200 | | 2(6x+5)=154 | | 7(1-x)=4x+40 | | 192/-64 | | H+3.8=12.9 | | 6+v/-3=-2/3 | | 5/4x+1/8x=5/8+x | | 8m+9=6m+19 | | -7/5y=-35 | | 7+1/7l=-2 | | -45=-9x+5 | | 26n+17=-42 | | 3n-1-5n=27 | | 192/-4*4*4 | | 2x+76=114 | | 4-1/2q=33-q | | -2x^2+9x-5=0 | | -7d=-42 | | 4-1/2=33-q | | 8n+6=34 | | -3x+10=13 | | 2/3a | | 2x+16=114 | | -3+10=13 | | 4.50x+8.25=1222.50 | | 3+4(7-9*9)= |